STUDENTS’ PARAPHRASING ABILITY IN ACADEMIC WRITING; TECHNIQUES AND CHALLENGES - Ririn Ovilia; Ainul Addinna; Rifky Oktoviandry (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2022)
In higher education, the demand of research publication is steadily growing.  Due to this fact, the skills to write academic paper must be improved as well. One of the foremost skills required in writing academic paper is paraphrasing. This qualitative study investigates the most frequents paraphrasing techniques used by students and their challenges during the paraphrasing process. Thirty students enrolled in Academic Writing class participated in this research.  The participants were required to do paraphrasing task, and 8 selected students (4 more proficient students and 4 less proficient students) would be interviewed in regards to their challenges in paraphrasing and how they dealt with such challenge. The result of paraphrasing task unveiled that most strategies used by students were “change to synonym”,  “change to active to passive form” and a combination of these two. In regards to the challenges, reading, lexical and syntactic problems are the main challenges addressed by participants.